Secularizarea şi naţionalizarea unui topos clasic: locus amoenus, Dimitrie Bolintineanu – Traianida - George Neagoe (Revista de Istorie și Teorie Literară)
In this study, we propose for analysis a topos of the classical literature – locus amoenus – treated in a romantic vision, based on the national epopee Traianida by Dimitrie Bolintineanu. The refuge in the past does not mean so much nostalgia, but especially the transformation of missing values in distant times – such as patriotism and heroism – into alternatives to the desolate present. Locus amoenus is conceived according to nation’s the needs, in fact the concept by which romantic intellectuals try to provide the optimal answers to the dilemmas, anxieties and problems of the community. The past receives utopian valence. The freedom and dignity of the Dacians, the mythical aura of the rulers like Decebalus and the respect that Dacia imposed on the Roman Empire are transformed for the purposes of Romania.